Strategic Human Resource Management Framework for State Universities and Colleges in the Philippines - Adrias, Ana Flor (International Journal of Scientific Research and Management (IJSRM), 2022)
State Universities and Colleges (SUC) in the Philippines are governed by their own Board of Regents while being mandated to comply with the guidelines set by Civil Service Commission (CSC). Despite CSC’s efforts to implement varied HR programs, SUCs still face major challenges in recruitment, selection and placement, and performance management.  Being exploratory in nature utilizing Grounded Theory methodology, in-depth interviews with ten human resource management officers were conducted. Results from the qualitative data showed that an HRMO’s role in addressing any strategic challenges was not optimized due to strategic, leadership, management, organizational value, and culture constraints. This paper concludes that HRMOs are compliance-oriented and that an HRMO’s initiative is an important enabling competency. Furthermore, this paper concludes with a Strategic Human Resource Management Framework for SUC that will enable HRMO to create better HR services for its stakeholders.